2021
DOI: 10.21203/rs.3.rs-526339/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of the Covid-19 Pandemic on Rhegmatogenous Retinal Detachment Treatment Patterns

Abstract: Background: To describe changes in rhegmatogenous retinal detachment (RRD) surgical procedures in Beijing during the COVID-19 pandemic. Material and Methods:A retrospective cohort of RRD patients was analyzed. Patients were divided into the COVID-19 pandemic group and pre-COVID-19 group according to their presentation. The presurgery characteristics, surgical procedures, and surgery outcomes were collected. The potential factors related to the choice of pars plana vitrectomy (PPV) or scleral buckling (SB) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The number of patients presenting with a macula-on retinal detachment was also lowest during the lockdown period in 2020 (39.2%) as compared to 2019 (50.0%) and 2021 (50.0%). These findings are in accordance with reports from other groups from many regions of the world including Europe, the USA, and Asia [21][22][23]. We assume that the slightly lower initial visual acuity reflects the macula status upon first presentation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The number of patients presenting with a macula-on retinal detachment was also lowest during the lockdown period in 2020 (39.2%) as compared to 2019 (50.0%) and 2021 (50.0%). These findings are in accordance with reports from other groups from many regions of the world including Europe, the USA, and Asia [21][22][23]. We assume that the slightly lower initial visual acuity reflects the macula status upon first presentation.…”
Section: Discussionsupporting
confidence: 92%
“…A similar situation was reported by Baudin and colleagues from France observing a decrease of 41.6% in the number of retinal detachment surgeries during the 8-week lockdown period in 2020 as compared to 2019. Similarly, a reduction in the number of cases as well as a prolonged time to surgery has been reported from Portugal and other regions of the world [20-22].…”
Section: Discussionmentioning
confidence: 67%
“…postoperative visual outcomes of these patients were also significantly worse than before [4][5][6][7].…”
Section: Introductionmentioning
confidence: 81%
“…Jørstad et al reported a COVID-19 outbreak in an ophthalmology department, resulting in six COVID-19 cases and a two-week standstill in clinical activity [14]. Previous studies also revealed that the sudden outbreak of COVID-19 could lead to decreased ophthalmic outpatient volumes and poorer general care in ophthalmology [15][16][17][18][19][20][21][22][23]. Despite the clear data of recession in ophthalmic medical care, the exact distribution of diseases that were affected the most was never discussed.…”
Section: Introductionmentioning
confidence: 99%